Staff Personnel Management Strategies of Principals for School Effectiveness in Private Secondary Schools in Anambra State Nigeria (Journal of Guidance and Counselling Studies, 2022)
The seeming ineffectiveness in secondary schools in Nigeria necessitated this study on staff personnel strategies of principals for school effectiveness in private secondary schools in  Awka South Local government area of Anambra State, Nigeria. The study adopted the descriptive survey research design. One research questions guided the study. The population of the study comprised 23 principals in the 23 private secondary schools in Anambra State. There was no sampling as the entire population was used for the study. A researcher’s developed questionnaire was the instrument used for data collection. The instrument was validated by three experts who are lecturers, two in Educational Measurement and Evaluation, Department of Educational Foundations and the other in Educational Management and Planning, Department of Educational Management and Policy all in the Faculty of Education Nnamdi Azikiwe University, Awka, Anambra State Nigeria.The Cronbach’s alpha method was used to determine the internal consistency of the items which yielded an overall reliability coefficient of 0.74. The researcher with the help of three research assistants distributed and successfully collected 23 copies of the questionnaire administered. The research questions were answered using the arithmetic mean. It was found among others that principals in private secondary schools in Awka south Local Government area of Anambra State adopt staff personnel strategies of principals for school effectiveness. Based on the findings of the study, it was recommended that private secondary schools should organize workshops and conferences for teachers towards school effectiveness.